Bactericidal and anti-biofilm effects of uncharged and cationic ultrasound-responsive nitric oxide microbubbles on Pseudomonas aeruginosa biofilms - LuTheryn, G; Hind, C; Campbell, C; Crowther, A; Wu, Q; Keller, SB; Glynne-Jones, P; Sutton, JM; Webb, JS; Gray, M; Wilks, SA; Stride, E; et al. (Frontiers Media, 2022)
Bacterial biofilms are a major and ongoing concern for public health, featuring both inherited genetic resistance traits and a conferred innate tolerance to traditional antibiotic therapies. Consequently, there is a growing need for novel methods of drug delivery, to increase the efficacy of antimicrobial agents. This research evaluated the anti-biofilm and bactericidal effects of ultrasound responsive gas-microbubbles (MBs) of either air or nitric oxide, using an in vitro Pseudomonas aeruginosa biofilm model grown in artificial wound medium. The four lipid-based MB formulations evaluated were room-air MBs (RAMBs) and nitric oxide MBs (NOMBs) with no electrical charge, as well as cationic (+) RAMBs+ and NOMBs+. Two principal treatment conditions were used: i) ultrasound stimulated MBs only, and ii) ultrasound stimulated MBs with a sub-inhibitory concentration (4 µg/mL) of the antibiotic gentamicin. The total treatment time was divided into a 60 second passive MB interaction period prior to 40 second ultrasound exposure; each MB formulation was tested in triplicate. Ultrasound stimulated RAMBs and NOMBs without antibiotic achieved reductions in biofilm biomass of 93.3% and 94.0%, respectively. Their bactericidal efficacy however was limited, with a reduction in culturable cells of 26.9% and 65.3%, respectively. NOMBs with sub-inhibitory antibiotic produced the most significant reduction in biofilm biomass, corresponding to a 99.9% (SD ± 5.21%); and a 99.9% (SD ± 0.07%) (3-log) reduction in culturable bacterial cells. Cationic MBs were initially manufactured to promote binding of MBs to negatively charged biofilms, but these formulations also demonstrated intrinsic bactericidal properties. In the absence of antibiotic, the bactericidal efficacy of RAMB+ and NOMB+ was greater that of uncharged counterparts, reducing culturable cells by 84.7% and 86.1% respectively; increasing to 99.8% when combined with antibiotic. This study thus demonstrates the anti-biofilm and bactericidal utility of ultrasound stimulated MBs, and specifically is the first to demonstrate the efficacy of a NOMB for the dispersal and potentiation of antibiotics against bacterial biofilms in vitro. Importantly the biofilm system and complex growth-medium were selected to recapitulate key morphological features of in vivo biofilms. The results us offer new insight for the development of new clinical treatments, for example, in chronic wounds.